Carbon Dioxide Emission and Soil Sequestration for the French Agro-Food System: Present and Prospective Scenarios - Le Noë, Julia; Billen, Gilles; Garnier, Josette (Frontiers in Sustainable Food Systems, 2019)
France is a major agricultural power, characterized by a high degree of regional specialization, either in stockless cash crop farming, exporting most of its intensive cereal production, or in intensive livestock farming highly dependent on foreign feed imports. This agricultural model is characterized by wide nutrient and carbon cycle opening and severe environmental pollution. Based on the nutrient accounting GRAFS model, two contrasted scenarios for the French agricultural system at the 2050 horizon have recently been designed and evaluated for their capacity to meet both the national population's food demand and environmental standards in terms of water pollution. The first scenario (O/S, for opening and specialization) assumes the continuation of the current trends of intensification, specialization, and opening to international markets. The second one (A/R/D, for autonomy, reconnection, and demitarian diet) assumes a radical change toward organic farming with diversification of crop rotations, reconnection of crop and livestock farming, and reduction of the proportion of animal proteins in the human diet. Herein we calculate the budget of CO2 emissions and C sequestration in soils of these two scenarios compared with the current situation of the French agro-food system, by coupling the GRAFS and AMG models. These simulations reveal that the overall CO2 emissions balance of the O/S scenario is far higher than those of the A/R/D, namely because of the emissions associated with mineral fertilizer manufacture, and imported feed and mechanization of land management requiring a large amount of fossil fuel. As the organic carbon content of the soil is known to be highly path-dependent (in the sense that it is the inheritance of previous land use practices), we tested the effect of two rates of implementation of the two scenarios and evaluated the response time of the C soil store, which is of the order of two decades or more. This reveals that after about two-three decades following the implementation of a scenario, an equilibrium is reached with no more net soil C emission nor sequestration.